Platelet-rich plasma and platelet-rich fibrin as a regenerative tool - Athiban Inbarajan (Wolters Kluwer Medknow Publications, 2021)
Platelet-rich plasma (PRP) and platelet-rich fibrin (PRF) are used as a valuable adjunct in the treatment of maxillofacial rehabilitation. PRP used along with growth hormone helps in bone healing and tissue regeneration in the areas affected by bone and soft tissue-related defects. It aids not only in faster and better healing of the surgically debrided area but also in regeneration of the bone at a faster rate. This review comprises the applications of PRP and PRF and their uses in various procedures.